Loss of invariant chain protects nonobese diabetic mice against type 1 diabetes. - Mellanby, R; Koonce, C; Monti, A; Phillips, J; Cooke, A; Bikoff, E (2006)
The invariant (Ii) chain acts as an essential chaperone to promote MHC class II surface expression, Ag presentation, and selection of CD4(+) T cells. We have examined its role in the development of type 1 diabetes in NOD mice and show that Ii chain-deficient NOD mice fail to develop type 1 diabetes. Surprisingly, Ii chain functional loss fails to disrupt in vitro presentation of islet Ags, in the context of NOD I-A(g7) molecules. Moreover, pathogenic effector cells could be shown to be present in Ii chain-deficient NOD mice because they were able to transfer diabetes to NOD.scid recipients. The ability of these cells to transfer diabetes was markedly enhanced by depletion of CD25 cells coupled with in vivo anti-CD25 treatment of recipient mice. The numbers of CD4(+)CD25(+)Foxp3(+) T cells in thymus and periphery of Ii chain-deficient NOD mice were similar to those found in normal NOD mice, in contrast to conventional CD4(+) T cells whose numbers were reduced. This suggests that regulatory T cells are unaffected in their selection and survival by the absence of Ii chain and that an alteration in the balance of effector to regulatory T cells contributes to diabetes prevention.